Factors that influence suffered of Low Back Pain (LBP) in MRI examination patients in Hospitals Semarang City - Sri Mulyati; Rini Indrati; Yeti Kartikasari; Jeffri Ardiyanto (Universitas 'Aisyiyah Yogyakarta, 2019)
Low back pain can be caused by a variety of musculosceletal diseases, psychological disorders and mobilization. Patients who performed MRI examinations were mostly caused by indications of Low Back Pain (LBP). LBP became an important problem in the United States, in Indonesia an estimated 40% of the population of Central Java aged over 65 years have suffered from low back pain, the prevalence in men is 18.2% and in women is 13.6%. In recent years, Magnetic resonance imaging (MRI) has been used widely, including for diagnosis of LBP. This study aims to identify factors that affect the suffered of low back pain in patients undergoing an MRI examination which consists of personal factors covering : age, habits, smoking exercise habits, height, obesity, and work factors (tenure, work duration). The research categorize as a quantitative research with cross-sectional design. This study used a sample of all cases of MRI examination with complaints of low back pain as many as 60 patients. Statistical tests using chi square and non-parametric Mann Whitney tests. From the results of the study found that those who suffer of LBP are mostly from personal factors covering : men, have jobs that have more burden (weight), more at the age of ≥ 35 years, no smoking, no exercise, height ≥ 163 cm, overweight / obesity, with tenure of ≥ 10 years, with a work duration ≥ 8 hours a day, and type of LBP suffered in the chronic categorized. The factors that caused LBP in this study were personal factors in the most dominant sequence is caused by age, smoking habits, exercise habits, height, BMI, tenure and work duration and type of LBP chronik.